Ruxolitinib treatment for myelofibrosis: Efficacy and tolerability in routine practice. Issue 11 (November 2015) - Ellis, Martin H.; Lavi, Noa; Mishchenko, Elena; Dally, Najib; Lavie, David; Courevitch, Anna; Gutwein, Odit; Bulvik, Shlomo; Braester, Andrei; Chubar, Evgeni; Tavor, Sigal; Duek, Adrian; et al.
Highlights: Ruxolitinib in routine is administered for broader indications than in clinical trials. The majority of patients achieved clinical benefits from ruxolitinib. At a median follow-up of 11 months, 85% of patients were still on therapy. Blood transfusion requirements were lower compared to previous studies. Ruxolitinib is effective and tolerated outside of highly monitored clinical studies. Abstract: Ruxolitinib has been shown in two randomized clinical trials to be effective in alleviating systemic symptoms and reducing spleen size in patients with myelofibrosis (MF). We retrospectively evaluated efficacy and tolerability of ruxolitinib in a cohort of unselected MF patients treated in routine clinical practice. One hundred and two patients who began ruxolitinib therapy were identified in 13 participating centers. Ninety three of the patients receiving ruxolitinib for at least 3 months were evaluated for treatment efficacy and toxicity. Median age at ruxolitinib initiation was 67 years. Indications for treatment were constitutional symptoms (15%), symptomatic splenomegaly (6%) or both (76%). Two patients received ruxolitinib for other indications. The median initial ruxolitinib dose was 30 mg/day. Median duration of therapy was 11 months. Eighty two patients (88.2%) responded to therapy, 76 (84.4%) patients had improvement in constitutional symptoms and 60 patients (70.6%) had reduction in spleen length. While on ruxolitinib, 30% of patients had grade 3–4 anemia and 12.9% of patients had grade 3–4 thrombocytopenia. Thirteen patients (14%) discontinued therapy. This analysis of a cohort of MF patients treated with ruxolitinib in routine clinical practice demonstrates the efficacy and tolerability of this drug outside of a highly monitored clinical trial setting.